2001 Conference Proceedings of the 23rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2001.1017285
|View full text |Cite
|
Sign up to set email alerts
|

RF safety of wires in interventional MRI: using a safety index

Abstract: With the rapid growth of interventional MRI, radiofrequency (RF) heating at the tips of guidewires, catheters, and other wireshaped devices has become an important safety issue. Previous studies have identified some of the variables that affect the relative magnitude of this heating but none could predict the absolute amount of heating to formulate safety margins. This study presents the first theoretical model of wire tip heating that can accurately predict its absolute value, assuming a straight wire, a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 17 publications
4
111
1
Order By: Relevance
“…This is in contrast with previous studies which used simple straight wires to model DBS leads and concluded that maximum power deposition always occurs at the tip of the wire [39-42]. Fig.9 shows the distribution of MaxSAR for a representative lead geometry at two different rotation angles (ID9: θ = 0°, θ = 90°).…”
Section: Resultsmentioning
confidence: 62%
“…This is in contrast with previous studies which used simple straight wires to model DBS leads and concluded that maximum power deposition always occurs at the tip of the wire [39-42]. Fig.9 shows the distribution of MaxSAR for a representative lead geometry at two different rotation angles (ID9: θ = 0°, θ = 90°).…”
Section: Resultsmentioning
confidence: 62%
“…Thus, while SAR is an important measure that is readily available on MR scanners, SAR alone is likely insufficient for adequately assessing the risk of MR imaging of internalized conductive structures. Yeung et al (23) attempted to address permissible SAR levels by modeling clinical situations where internal conductors exist. They proposed that a “safety index” could be obtained for most situations whereby the permitted SAR level would be adjusted according to the potential for locally elevated SAR levels.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to limit heating by limiting the energy delivered by the imaging pulse sequence [47]. The excitation flip angle relates to heating quadratically, and lengthening the repetition time reduces heating proportionally [48].…”
Section: Pre-clinical Applications and Challenges To Clinical Translamentioning
confidence: 99%